The Implementationof of Reference Services on the Library of State Universities in Surabaya - Dharma, Gumelar Satya; Dwi P, Andri; Anggraeni, Dini; Fuadilah, Risma; Irlando K, Rona; Rahma P, Mega; Firda, Meyrinda; Setiawan, Agus; Yusna, Darista; Islahnia, Nindhita; Putri, Bella Savira; Ghani, Aditya Ahmad; Eko, Septian (Record and Library Journal, 2015)
Reference servicein the library is a service directly to relatethe reader. Reference service aims to help users to refer the source of the information sought for the benefit of study and research. The study,prepared by the method of quantitative descriptive approach was developed with the aim to determine the implementation of services based on collections, services, infrastructure and human resources in reference services in libraries public University state of Surabaya(UNESA),Airlangga University(UNAIR), Islamic University of Sunan Ampel(UINSA), UPN and Institute Technology of Sepuluh Nopember(ITS). Besides wanting to know the purpose of implementation of this research is to determine the constraints that exist in each service reference. Respondents in this study is a reference librarian from library public university State of Surabaya. Data collection methods used in this study by using the interview and observe an object of research in the form of library reference services in all public universities in the city of Surabaya. Based on observations on the entire library of public universities in Surabaya, most can be said is still low in the service of providing information through reference services, which still lack the activities provided librarians to the user, the user is not maximized in utilizing the service even collections of reference services. Because users prefer to search for electronic information through online media, so the impact is not utilization of the collection of books in a reference service, where the phenomenon is a major hurdle for library reference services public universities in Surabaya today. Solutions that can be taken to overcome the existing problems that the library should add some activities such as guidance pemustaka reference services, guidance and also conduct searches of e-services The reference to address users who prefer a source of information in electronic form than printed form.